Pengaruh Pupuk Limbah Cair Tahu dari Produsen yang Berbeda terhadap Pertumbuhan Tanaman Cabai Merah Keriting - Marchelina, Shally; Jabbar, Abdul (ECOTAS, 2025)
Tofu industry waste consists of solid and liquid waste. Tofu liquid waste contains high organic materials such as C, H, O, N, P, and S, which are useful as nutrients for plants. This study was conducted to see the difference in the effectiveness of liquid organic fertilizer from tofu liquid waste, considering that the levels of elements in each production unit are not the same. In this study, the effectiveness test was carried out on curly red chili plants (Capsicum annum L.). The experiment was carried out with a simple randomized block design and the data obtained were analyzed by the F test with a level of 5% if there was a significant difference followed by a 5% BNT test. Based on the analysis of variance, it is known that the growth of curly red chili plants (Capsicum annum L.) including plant height, number of leaves, stem diameter, and leaf diameter is influenced by the provision of fertilizer and the type of waste as the basic material for fertilizer. While the wet weight and length of plant roots are not affected by the provision of fertilizer or the type of waste.